Husbands Remain as Imāms: The Phenomenon of House Husband in Yogyakarta and Ponorogo, Indonesia - Qibtiyah, Alimatul; Shina, Arya Fendha Ibnu; Restendy, Mochammad Sinung; Muafiah, Evi; Tavip Hayati, Evi Septiani (Al-Ahwal: Jurnal Hukum Keluarga Islam, 2024)
A house husband refers to the involvement of a husband or father in household and parenting tasks. This research aims to reveal the phenomenon of house husbands and examine the attitudes of government, religious, and community leaders toward this flexible gender role. This study employs mixed methods, including a survey of 100 respondents (50 men and 50 women), in-depth interviews, focus group discussions (FGDs), and documentation. The research found that the trend of house husbands is increasing. This indicates that the patriarchal culture, which assigns domestic and nurturing tasks exclusively to women, is becoming less relevant. The rising number of house husbands aligns with the increasing participation of women in economic activities. The self-concept of husbands and wives shows a significant positive correlation with their attitudes toward the house husband phenomenon. The more positive their attitudes are toward this phenomenon, the happier they tend to be. Religious, community, and government leaders generally do not object to husbands' participation in domestic and parenting tasks. However, most respondents still believe that the leader of the family is the male or husband, except in specific situations—such as when the husband is seriously ill—that necessitate the reversal of roles. [House husband (suami ‘rumahan’) mengacu pada keterlibatan seorang suami atau ayah dalam tugas-tugas rumah tangga dan pengasuhan anak. Penelitian ini bertujuan untuk mengungkap fenomena house husband dan menganalisis sikap pemerintah, tokoh agama, serta tokoh masyarakat terhadap fenomena peran gender yang fleksibel ini. Penelitian ini menggunakan metode campuran, termasuk survei terhadap 100 responden (50 laki-laki dan 50 perempuan), wawancara mendalam, diskusi kelompok terfokus (FGD), dan dokumentasi. Hasil penelitian menunjukkan bahwa tren house husband mengalami peningkatan. Hal ini menunjukkan bahwa budaya patriarki, yang menetapkan tugas domestik dan pengasuhan hanya sebagai tanggung jawab perempuan, semakin tidak relevan. Peningkatan jumlah house husband sejalan dengan meningkatnya partisipasi perempuan dalam kegiatan ekonomi. Konsep diri suami dan istri memiliki korelasi positif yang signifikan dengan sikap mereka terhadap fenomena house husband. Semakin positif sikap mereka terhadap fenomena ini, semakin tinggi tingkat kebahagiaan mereka. Para tokoh agama, masyarakat, dan pemerintah pada umumnya tidak mempermasalahkan partisipasi suami dalam tugas-tugas rumah tangga maupun pengasuhan anak. Namun, sebagian besar responden masih berpendapat bahwa kepala keluarga adalah laki-laki atau suami, kecuali dalam situasi tertentu—seperti ketika suami mengalami sakit parah—yang mengharuskan peran tersebut diambil-alih oleh perempuan.]